Supplier segmentation: A systematic literature review - Fallah Lajimi, Hamidreza; Majidi, Sara (Journal of Supply Chain Management Science, 2021)
Supplier Segmentation is one of the key activities of supplier relationship management (SRM) for companies with a large number of suppliers. It involves dividing the suppliers into a manageable number of segments, to formulate SRM strategies for the various segments, rather than for each individual supplier. In recent years, supplier segmentation has drawn the attention of a number of researchers. The aim of this study is to provide a systematic review of existing literature on supplier segmentation and identify the future trend in this research area using a combination of Systematic Literature Review (SLR) and Citation Network Analysis (CNA). After determining the search protocol and paper selection indexes, 52 papers were eventually selected, and analyzed, in accordance with the steps proposed in the SLR and CNA methods. The results show that researchers tend to favor the portfolio-involvement approach and decision-making techniques in supplier segmentation research domain. A comprehensive analysis of the studies made it possible to distill the future research trend. This research area requires further study involving the supply chain paradigms, the impact of supplier segmentation on performance, and the analysis of the supplier relationship management as a whole, with supplier segmentation being one of its components.